Optimal Design of Rectification Circuit in Electronic Circuit Fault Self‐repair Based on EHW and RBT. Issue 1 (1st January 2018) - Zhang, Junbin; Cai, Jinyan; Meng, Yafeng
Abstract : Reliability of traditional electronic circuit is improved mainly by redundant fault‐tolerant technology with large hardware resource consumption and limited fault self‐repair capability. In complicated environment, electronic circuit faults appear easily. If on‐site immediate repair is not implemented, normal running of electronic system will be directly affected. In order to solve these problems, Evolvable hardware (EHW) technology is widely used. The conventional EHW has some bottlenecks. The optimal design of Rectification circuit (RTC) is further researched on the basis of the previously proposed fault self‐repair based on EHW and Reparation balance technology (RBT). Fault sets are selected by fault danger degree and fault coverage rate. The optimal designed RTC can completely repair faults in the fault set. Simulation results prove that it has higher self‐repair capability and less hardware resource.